Coffee Price Trends Over Time: An Analysis of Market Dynamics in Slovenia (1990–2023) - Vukovič, Goran; Raspor, Andrej (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
In this paper, we investigated whether retail prices are rising faster than inflation and how much price increases consumers are willing to accept. Using the historical method, we analyzed data on global stock market prices and retail coffee prices in Slovenia between 1990 and 2024. In addition, we conducted an online survey with 536 participants. We found that retail prices increased by 40% more than inflation. The analysis showed that there were no statistically significant differences in tolerance for higher prices by municipality, settlement size, or gender. However, older consumers are slightly more tolerant of price increases.